Kontribusi Ekspektasi Karier, Motivasi Kerja, dan Pengalaman Kerja Terhadap Kesiapan Kerja Siswa Kelas XII SMK Duta Bangsa - N.P. Antariati; K.R. Dantes; I.G.K.R. Sunu (Pascasarjana Universitas Pendidikan Ganesha, 2021)
This examination means to decide and investigate the concurrent commitment of profession assumptions, work inspiration, and modern work insight to the work status of understudies of SMK DUTA BANGSA. This exploration is an ex-post facto research. The populace that was additionally utilized as an example in this investigation was 44 understudies. Information were gathered utilizing a survey. Information examination utilized numerous relapse, different relationship, and fractional connection. The aftereffects of this investigation uncovered that: 1). There is a huge commitment of profession assumptions to the work status of SMK DUTA BANGSA understudies, 2). There is a critical commitment of work inspiration to the work status of SMK DUTA BANGSA understudies, 3). There is a huge commitment of work insight to the work status of SMK DUTA BANGSA understudies, 4). There is a critical commitment between profession assumptions, work inspiration, and work insight on understudy work preparation at the same time. In light of the consequences of the investigation, it tends to be presumed that vocation assumptions, work inspiration, and work experience make a huge commitment to the work preparation of SMK DUTA BANGSA understudies both independently and all the while.